Productive Waqf Law Reform: A Solution to Support Indonesian Local Economy amid Contemporary Global Recession - Miftahul Huda; Aditya Prastian Supriyadi; Ramadhita (MILRev: Metro Islamic Law Review, 2025)
Productive waqf potential supports sustainable local economic resilience in the face of a global recession. However, its management in Indonesia remains suboptimal, considering that waqf assets are more dominantly distributed to non-productive sectors. This happens because the legal framework of waqf is not ideal for regulating the management of cash waqf assets productively for the economic empowerment of the community amid a global recession. This study analyses the urgency of legal reform in the cash waqf asset sector to support local economic empowerment while exploring the synergy between Islamic law and positive law in designing a more adaptive basis for productive waqf law to address modern economic challenges. The method employed in this study is normative legal research, incorporating both conceptual and statutory approaches. The data analysis technique was conducted using the content analysis method to explore legal doctrines and related literature to formulate the ideal concept of productive waqf legal reform. The research results show that the urgency of waqf law reform is based on weak regulations that hinder the optimisation of cash waqf assets for economic empowerment. Legal uncertainty, inequality of access to waqf benefits, and regulatory compliance with the needs of the modern economy are the main challenges that require responses. The second area of research on the synergy between Islamic law and positive law can serve as the basis for regulatory renewal through the accommodation of sharia maqashid principles, economic empowerment based on productive waqf, and collaboration among the government, the private sector, and the community. Proper legal reform will encourage more structured and systematic management of cash waqf assets, making it a strategic legal instrument for strengthening local economic resilience amid the threat of a global recession.